2007
DOI: 10.2105/ajph.2005.081083
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Differences in the Impact of HIV Infection on Workforce Participation in France in the Era of Highly Active Antiretroviral Therapy

Abstract: Objectives. We sought to measure the difference in employment rates between HIV-seropositive and HIV-seronegative persons and to establish whether this difference varied according to the HIV-infected persons’ socioeconomic position as defined by education level. Methods. We used data from the VESPA (VIH: Enquête Sur les Personnes Atteintes) study, a large cross-sectional survey conducted among a nationally representative sample of 2932 HIV-infected patients in France. Age-, gender-, nationality-, and educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 41 publications
2
15
1
5
Order By: Relevance
“…According to some studies, 41% to 45% of adults with HIV are unemployed (Dray-Spira, Gueguen, Ravaud, & Lert, 2007; Rabkin et al, 2004). As mentioned earlier, in one sample of 141 gay men with HIV, only 20% were continuously employed full-time over a 30-month period (Rabkin et al).…”
Section: Employment and Hivmentioning
confidence: 99%
“…According to some studies, 41% to 45% of adults with HIV are unemployed (Dray-Spira, Gueguen, Ravaud, & Lert, 2007; Rabkin et al, 2004). As mentioned earlier, in one sample of 141 gay men with HIV, only 20% were continuously employed full-time over a 30-month period (Rabkin et al).…”
Section: Employment and Hivmentioning
confidence: 99%
“…Although the disease mostly affects a population of working age, studies have reported persistent high unemployment rates among those living with HIV/AIDS in the era of HAART, ranging from 45% to 65% 2329. HIV infection may constitute a barrier to access (or return) to work for those unemployed and/or a cause of employment loss for those in work through phenomena including health status alterations, HIV-related discrimination from employers/colleagues and difficulties in coping with the condition and work demands at the same time.…”
mentioning
confidence: 99%
“…Le capital éducatif et l'activité professionnelle permettent de conserver les conditions d'une vie la plus normale possible malgré la maladie. L'activité professionnelle n'a pas été prise en compte ici, car elle est très liée aux autres caractéristiques individuelles (niveau d'étude, nationalité) et à l'état de santé [15,16] a été en général acquis antérieurement au diagnostic. Les résul-tats concernant l'association avec la cohabitation en couple ne sont pas clairs : on observe plus de couples cohabitants chez les hommes hétérosexuels de niveau bac que chez les hommes ayant fait des études universitaires, une tendance similaire chez les femmes, et pas de relation pour les homosexuels.…”
Section: Discussionunclassified